Lead nickelate niobate-based electrostrictive ceramic as well as preparation method and application thereof
By introducing heterovalent neodymium ions into lead niobium niacitate-based relaxation ferroelectric ceramic materials, it destroys its long-range ordered ferroelectric domain structure, and solves the problem of strain hysteresis in the application of high-precision drive field, and achieves high dielectric and electrostrictive performance ceramic materials, suitable for high precision components.
Patent Information
- Application Number
- CN202411758598.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-04-11
AI Technical Summary
The existing lead niobium niacitate-based relaxation ferroelectric ceramic materials are limited in the application of high-precision and fast response driving fields, mainly because the field-induced strain curve will produce a hysteresis effect under the action of irreversible domain wall motion, affecting the output accuracy of the piezoelectric driver.
Through the doping of idiovalent neodymium ion, the position of the A-position divalent lead ions in the perovskite structure is replaced, causing distortion of the unit cell structure, enhancing the volume content of polar nanomicro regions, and destroying the long-range ordered ferroelectric domain structure, reducing the strain hysteresis coefficient caused by irreversible domain wall motion.
It has achieved a ceramic material with high dielectric and electrostrictive properties. The electrostrictive strain is as high as 0.112-0.143% at an electric field of 20kV/cm, and the room temperature dielectric constant εr is as high as 28300-30020, which is suitable for the field of high precision components.
Smart Images

Figure CN119797915A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional ceramics, and in particular relates to a lead nickel niobate-based electrostrictive ceramic and a preparation method and application thereof. Background Art
[0002] Electrostriction refers to the phenomenon that dielectrics undergo elastic deformation in an electric field, which can occur in all dielectrics. When an external electric field acts on a dielectric, the dielectric molecules are polarized and arranged along the direction of the electric field. Due to the mutual attraction between the positive and negative electrodes, the dielectric shrinks or stretches in this direction until the elastic force inside it reaches a balance with the electric attraction. Since the electrostrictive effect is a secondary effect, it is extremely weak in piezoelectric ceramics without a symmetric center. The strain generated under the same driving electric field is much smaller than the strain generated by the inverse piezoelectric effect, so it is often ignored by researchers. However, electrostrictive ceramic materials have the advantages of high displacement resolution, small size, and fast response speed. In the actual driving process, they show the characteristics of no noise, no heat, and low energy consumption. They can be used to manufacture high-precision sensors, micro-displacers and positioners, etc., to achieve precise control of small displacements. Especially in recent years, with the rapid development of nanotechnology and micro-control technology, electrostrictive materials play an increasingly important role. The research and development of high-performance electrostrictive ceramic materials has become one of the hot spots that countries are committed to research and development.
[0003] As a typical electrostrictive material, lead magnesium niobate Pb (Mg 1 / 3 Nb 2 / 3 )O3(PMN) and lead zinc niobate Pb(Zn 1 / 3Nb 2 / 3 )O3(PZN) based relaxor ferroelectric materials have received extensive attention and research in recent years. Among them: solid solutions of lead magnesium niobate and lead titanate, especially 0.9Pb(Mg 1 / 3 Nb 2 / 3 )O3-0.1PbTiO3 ceramics have attracted much attention due to their excellent dielectric and electrostrictive properties. Their electrostrictive strain is as high as 0.12% under an electric field of 35kV / cm. 0.9Pb(Mg 1 / 3 Nb 2 / 3 The excellent electrostrictive properties of )O3-0.1PbTiO3 ceramics are mainly derived from the random occupation of different valence ions at the B position of the perovskite structure (ABO3), resulting in a microscopic uneven distribution of chemical components, which further leads to the generation of polarized micro-regions at the nanoscale. The size of the polar nano-microregions is small, and their polarization direction can easily deflect under the action of the external electric field, inducing strain. At the same time, after the external electric field is removed, it can spontaneously return to the state of random orientation before polarization, thus presenting a high-performance electrostrictive curve without hysteresis coefficient.
[0004] Lead Niobate Pb(Ni 1 / 3Nb 2 / 3 )O3 is a B-site composite perovskite structure relaxor ferroelectric with a Curie temperature of -120°C, which is much lower than the Curie temperature of PMN and PZN systems. Its unique properties have potential advantages in the component design of electrostrictive materials. 1 / 3 Nb 2 / 3 )O3-PbTiO3 (PNN-PT) is a relaxor ferroelectric ceramic material composed of lead nickel niobate and lead titanate, which has high dielectric and piezoelectric properties. Its piezoelectric coefficient near the quasi-modular phase boundary 0.66PNN-0.34PT is as high as 500pC / N. This excellent piezoelectric property makes it have broad application prospects in the fields of sensors, drivers and transducers. However, its field-induced strain curve will produce a hysteresis effect under the action of irreversible domain wall motion. This hysteresis effect will affect the output accuracy of the piezoelectric driver, which limits the application of PNN-PT ceramics in the field of high-precision and fast-response driving. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a lead nickel niobate-based electrostrictive ceramic and a preparation method and application thereof, wherein the lead nickel niobate-based electrostrictive ceramic has high dielectric and electrostrictive properties, and the electrostrictive strain is as high as 0.112-0.143% under an electric field of 20 kV / cm, and the room temperature dielectric constant ε r As high as 28300-30020, its excellent electrostrictive performance has broad application prospects in the field of high-precision components.
[0006] In order to solve the above technical problems, the first aspect of the present invention provides a lead nickel niobate-based electrostrictive ceramic, the chemical formula of the lead nickel niobate-based electrostrictive ceramic is: Pb (1-y) Nd y (Ni 1 / 3 Nb 2 / 3 ) (1-x) Ti x O3, where: 0.31≤x≤0.37, 0.015≤y≤0.030.
[0007] The study found that although the field-induced strain curve of the relaxor ferroelectric ceramic material (PNN-PT) composed of lead nickel niobate and lead titanate will produce a hysteresis effect under the action of irreversible domain wall motion, affecting the output accuracy of the piezoelectric driver. However, compared with the piezoelectric effect, the deformation of PNN-PT ceramics caused by the electrostrictive effect has the characteristics of low hysteresis and long life. Therefore, the present invention adopts heterovalent neodymium ion doping to replace the divalent lead ion (Pb 2+) position, by introducing a heterovalent ion with a smaller ionic radius into the A position of the PNN-PT ceramic, the unit cell structure can be distorted, the volume content of polar nano-domains in the lead nickel niobate-based relaxor ferroelectric ceramics can be enhanced, and its long-range ordered ferroelectric domain structure can be destroyed, further reducing the strain hysteresis coefficient caused by the irreversible domain wall motion, thereby obtaining a ceramic material with both high dielectric and electrostrictive properties.
[0008] The second aspect of the present invention provides a method for preparing a lead nickel niobate-based electrostrictive ceramic, which is used to prepare the lead nickel niobate-based electrostrictive ceramic described in the first aspect, comprising the following steps:
[0009] (1) PbO, NiO, Nb2O5, TiO2, and Nd2O3 are mixed in a stoichiometric ratio according to the general chemical formula, and the mixture is ball-milled, dried, and pre-calcined to obtain a pre-calcined powder;
[0010] (2) adding an organic binder to the pre-calcined powder, and sequentially performing ball milling, drying, sieving, and pressing to obtain a ceramic green body;
[0011] (3) debinding the ceramic green body and then sintering it to obtain a dense ceramic;
[0012] (4) Polishing and silvering the surface of the dense ceramic to obtain the lead nickel niobate-based electrostrictive ceramic.
[0013] Specifically, when preparing the lead nickel niobate-based electrostrictive ceramic of the present invention, the raw materials are first mixed in a stoichiometric ratio and then pre-fired. The raw materials are reacted by a solid phase synthesis method to obtain a stable pre-fired powder with a perovskite structure, so as to reduce the generation of impurities in the later sintering process, thereby laying a foundation for preparing ceramic materials with high dielectric constant and electrostrictive strain.
[0014] In some embodiments of the present invention, in step (1) and step (2), the ball milling medium is anhydrous ethanol or water.
[0015] In some embodiments of the present invention, in step (1) and step (2), the mass ratio of the ball-milled material to the ball-milled medium is 1:(1-1.5).
[0016] In some embodiments of the present invention, in step (1) and step (2), the rotation speed of the ball mill is 200-300 r / min.
[0017] In some embodiments of the present invention, in step (1) and step (2), the ball milling time is 12-24 hours.
[0018] In some embodiments of the present invention, in step (1), the pre-calcination temperature is 850-950°C.
[0019] In some embodiments of the present invention, in step (1), the pre-burning time is 2-4 hours.
[0020] In some embodiments of the present invention, in step (2), the organic binder is selected from Rhoplex solution.
[0021] In some embodiments of the present invention, in step (2), the amount of the organic binder added is 2-4 wt % of the pre-calcined powder.
[0022] In some embodiments of the present invention, in step (3), the debinding temperature is 500-700° C. to remove the organic binder.
[0023] In some embodiments of the present invention, in step (3), the heating rate of the debinding is 1-2°C / min.
[0024] In some embodiments of the present invention, in step (3), the debinding holding time is 1-2 hours.
[0025] In some embodiments of the present invention, in step (3), the sintering temperature regime is: heating to 1190-1250°C at a rate of 2-5°C / min, keeping the temperature for 1-2 hours; and then naturally cooling to room temperature.
[0026] The room temperature referred to in the present invention refers to 25±5°C.
[0027] A third aspect of the present invention provides an electronic component, comprising the lead nickel niobate-based electrostrictive ceramic described in the first aspect.
[0028] In some embodiments of the present invention, the electronic components include high-precision sensors, micro-displacement drivers or positioners.
[0029] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:
[0030] (1) The present invention selects PNN-PT relaxor ferroelectric ceramic material with high dielectric and piezoelectric properties as the matrix, and adopts heterovalent ion doping to introduce heterovalent neodymium ions with small ion radius into the A position of PNN-PT ceramics, thereby causing the distortion of the unit cell structure, enhancing the volume content of polar nano-micro-regions in lead nickel niobate-based relaxor ferroelectric ceramics, and destroying its long-range ordered ferroelectric domain structure, further reducing the strain hysteresis coefficient caused by irreversible domain wall movement, and obtaining a ceramic material with both high dielectric and electrostrictive properties. The electrostrictive strain is as high as 0.112-0.143% under an electric field of 20kV / cm, and the room temperature dielectric constant ε rAs high as 28300-30020, its excellent electrostrictive performance has broad application prospects in the field of high-precision components.
[0031] (2) The present invention adopts the traditional solid phase synthesis method to prepare the neodymium ion doped lead nickel niobate based electrostrictive ceramics, and the preparation method is simple and suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 is a strain diagram of the lead nickel niobate-based electrostrictive ceramic prepared in Example 1;
[0033] Figure 2 is a strain diagram of the lead nickel niobate-based electrostrictive ceramic prepared in Example 2;
[0034] Figure 3 is a strain diagram of the lead nickel niobate-based electrostrictive ceramic prepared in Example 3;
[0035] Figure 4 is a strain diagram of the lead nickel niobate-based ceramic prepared in Comparative Example 1;
[0036] Figure 5 This is the strain diagram of the lead nickel niobate-based ceramic prepared in Comparative Example 2. DETAILED DESCRIPTION
[0037] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods not mentioned in detail are all process steps or preparation methods known to those skilled in the art.
[0038] Example 1
[0039] A lead nickel niobate-based electrostrictive ceramic, the chemical formula of which is: Pb 0.985 Nd 0.015 (Ni 1 / 3 Nb 2 / 3 ) 0.69 Ti 0.31 The preparation method of the lead nickel niobate-based electrostrictive ceramic comprises the following steps:
[0040] (1) According to the chemical formula Pb 0.985 Nd 0.015 (Ni 1 / 3 Nb 2 / 3 ) 0.69 Ti0.31 PbO, NiO, Nb2O5, TiO2, and Nd2O3 were weighed in a stoichiometric ratio of 1:1. The raw materials were then placed in a ball mill for 12 hours (the medium for ball milling was anhydrous ethanol, and the mass ratio of the material to anhydrous ethanol was 1:1). The raw materials were then placed in a 100°C oven for drying, and finally placed in an alumina crucible and pre-calcined at 950°C for 2 hours to obtain a pre-calcined powder.
[0041] (2) adding Rhoplex binder to the pre-calcined powder obtained in step (1) (the amount of binder added is 4 wt% of the mass of the pre-calcined powder), then placing it in a ball mill for ball milling for 12 hours (the medium for ball milling is anhydrous ethanol, and the mass ratio of the material to anhydrous ethanol is 1:1), then placing it in a 100° C. oven for drying, and finally placing it in an agate mortar for grinding, sieving, and pressing to obtain a ceramic green body;
[0042] (3) placing the ceramic green body obtained in step (2) into a muffle furnace, heating the temperature to 600° C. at a rate of 1° C. / min and keeping the temperature for 2 hours to remove the binder; then heating the temperature to 1250° C. at a rate of 2° C. / min, keeping the temperature for 2 hours, and cooling the temperature naturally to obtain a dense ceramic;
[0043] (4) The dense ceramic obtained in step (3) was ground and polished to a thickness of 1.2 mm, and then both sides of the polished dense ceramic were silvered to obtain the lead nickel niobate-based electrostrictive ceramic sample of this embodiment.
[0044] Performance testing and characterization:
[0045] (1) The dielectric properties of the lead nickel niobate-based electrostrictive ceramic sample prepared in Example 1 were tested, and the dielectric constant was 28720 at room temperature of 1 kHz.
[0046] (2) The electrostrictive strain performance of the lead nickel niobate-based electrostrictive ceramic sample prepared in Example 1 was tested. The results are as follows: Figure 1 As shown, where: Figure 1 The horizontal axis "Electric field" represents the applied electric field, and the vertical axis "Strain" represents the strain. Figure 1 It can be seen that under different voltages, the strain curves all show hysteresis-free electrostrictive curves, which can demonstrate high-precision characteristics in driver applications. Under an electric field of 20 kV / cm, the electrostrictive strain is 0.112%.
[0047] Example 2
[0048] A lead nickel niobate-based electrostrictive ceramic, the chemical formula of which is: Pb 0.975 Nd 0.025 (Ni 1 / 3 Nb 2 / 3 )0.66 Ti 0.34 The preparation method of the lead nickel niobate-based electrostrictive ceramic comprises the following steps:
[0049] (1) According to the chemical formula Pb 0.975 Nd 0.025 (Ni 1 / 3 Nb 2 / 3 ) 0.66 Ti 0.34 PbO, NiO, Nb2O5, TiO2, and Nd2O3 were weighed in a stoichiometric ratio of 1:100°C, and then each raw material was placed in a ball mill for 24 hours (the medium for ball milling was anhydrous ethanol, and the mass ratio of the material to anhydrous ethanol was 1:1.2), and then placed in a 100°C oven for drying, and finally placed in an alumina crucible and pre-calcined at 900°C for 4 hours to obtain a pre-calcined powder.
[0050] (2) adding Rhoplex binder to the pre-calcined powder obtained in step (1) (the amount of binder added is 2 wt% of the mass of the pre-calcined powder), then placing it in a ball mill for 24 hours (the medium for ball milling is anhydrous ethanol, and the mass ratio of the material to anhydrous ethanol is 1:1.2), then placing it in a 100° C. oven for drying, and finally placing it in an agate mortar for grinding, sieving, and pressing to obtain a ceramic green body;
[0051] (3) placing the ceramic green body obtained in step (2) into a muffle furnace, heating the temperature to 500° C. at a rate of 2° C. / min and keeping the temperature for 2 hours to remove the binder; then heating the temperature to 1220° C. at a rate of 5° C. / min, keeping the temperature for 2 hours, and cooling the temperature naturally to obtain a dense ceramic;
[0052] (4) The dense ceramic obtained in step (3) was ground and polished to a thickness of 1.2 mm, and then both sides of the polished dense ceramic were silvered to obtain the lead nickel niobate-based electrostrictive ceramic sample of this embodiment.
[0053] Performance testing and characterization:
[0054] (1) The lead nickel niobate-based electrostrictive ceramic sample prepared in Example 2 was subjected to a dielectric property test, and the dielectric constant was 30020 at room temperature of 1 kHz.
[0055] (2) The electrostrictive strain performance of the lead nickel niobate-based electrostrictive ceramic sample prepared in Example 2 was tested. The results are as follows: Figure 2 As shown, from Figure 2 It can be seen that under different voltages, the strain curves all show hysteresis-free electrostrictive curves, which can demonstrate high-precision characteristics in driver applications. Under an electric field of 20 kV / cm, the electrostrictive strain is 0.127%.
[0056] Example 3
[0057] A lead nickel niobate-based electrostrictive ceramic, the chemical formula of which is: Pb 0.97 Nd 0.03 (Ni 1 / 3 Nb 2 / 3 ) 0.63 Ti 0.37 The preparation method of the lead nickel niobate-based electrostrictive ceramic comprises the following steps:
[0058] (1) According to the chemical formula Pb 0.97 Nd 0.03 (Ni 1 / 3 Nb 2 / 3 ) 0.63 Ti 0.37 PbO, NiO, Nb2O5, TiO2, and Nd2O3 were weighed in a stoichiometric ratio of 1:100°C, and then each raw material was placed in a ball mill for 12 hours (the medium for ball milling was anhydrous ethanol, and the mass ratio of the material to anhydrous ethanol was 1:1.5), and then placed in a 100°C oven for drying, and finally placed in an alumina crucible and pre-calcined at 850°C for 4 hours to obtain a pre-calcined powder.
[0059] (2) adding Rhoplex binder to the pre-calcined powder obtained in step (1) (the amount of binder added is 4 wt% of the mass of the pre-calcined powder), then placing it in a ball mill for ball milling for 12 hours (the medium for ball milling is anhydrous ethanol, and the mass ratio of the material to anhydrous ethanol is 1:1), then placing it in a 100° C. oven for drying, and finally placing it in an agate mortar for grinding, sieving, and pressing to obtain a ceramic green body;
[0060] (3) placing the ceramic green body obtained in step (2) into a muffle furnace, heating the temperature to 700° C. at a rate of 2° C. / min and keeping the temperature for 2 hours to remove the binder; then heating the temperature to 1190° C. at a rate of 5° C. / min, keeping the temperature for 2 hours, and cooling the temperature naturally to obtain a dense ceramic;
[0061] (4) The dense ceramic obtained in step (3) was ground and polished to a thickness of 1.2 mm, and then both sides of the polished dense ceramic were silvered to obtain the lead nickel niobate-based electrostrictive ceramic sample of this embodiment.
[0062] Performance testing and characterization:
[0063] (1) The lead nickel niobate-based electrostrictive ceramic sample prepared in Example 1 was subjected to a dielectric property test, and the dielectric constant was 28300 at room temperature of 1 kHz.
[0064] (2) The electrostrictive strain performance of the lead nickel niobate-based electrostrictive ceramic sample prepared in Example 1 was tested. The results are as follows: Figure 3 As shown, from Figure 3 It can be seen that under different voltages, the strain curves all show hysteresis-free electrostrictive curves, which can demonstrate high-precision characteristics in driver applications. Under an electric field of 20 kV / cm, the electrostrictive strain is 0.143%.
[0065] Comparative Example 1
[0066] A lead nickel niobate-based ceramic, the chemical formula of which is: Pb(Ni 1 / 3 Nb 2 / 3 ) 0.66 Ti 0.34 The preparation method of the lead nickel niobate-based ceramic comprises the following steps:
[0067] (1) According to the chemical formula Pb(Ni 1 / 3 Nb 2 / 3 ) 0.66 Ti 0.34 PbO, NiO, Nb2O5, and TiO2 were weighed in a stoichiometric ratio of O3, and then each raw material was put into a ball mill for 24 hours (the medium of the ball mill was anhydrous ethanol, and the mass ratio of the material to anhydrous ethanol was 1:1.2), and then dried in a 100°C oven, and finally put into an alumina crucible and pre-calcined at 900°C for 4 hours to obtain a pre-calcined powder;
[0068] (2) adding Rhoplex binder to the pre-calcined powder obtained in step (1) (the amount of binder added is 2 wt% of the mass of the pre-calcined powder), then placing it in a ball mill for 24 hours (the medium for ball milling is anhydrous ethanol, and the mass ratio of the material to anhydrous ethanol is 1:1.2), then placing it in a 100° C. oven for drying, and finally placing it in an agate mortar for grinding, sieving, and pressing to obtain a ceramic green body;
[0069] (3) placing the ceramic green body obtained in step (2) into a muffle furnace, heating the temperature to 500° C. at a rate of 2° C. / min and keeping the temperature for 2 hours to remove the binder; then heating the temperature to 1220° C. at a rate of 5° C. / min, keeping the temperature for 2 hours, and cooling the temperature naturally to obtain a dense ceramic;
[0070] (4) The dense ceramic obtained in step (3) was ground and polished to a thickness of 1.2 mm, and then both sides of the polished dense ceramic were silvered to obtain the lead nickel niobate-based ceramic sample of this comparative example.
[0071] Performance testing and characterization:
[0072] (1) The dielectric properties of the lead nickel niobate-based ceramic sample prepared in Comparative Example 1 were tested, and the dielectric constant at room temperature of 1 kHz was 7120. Comparing Example 2 with Comparative Example 1, it can be seen that the doping of Nd ions greatly increases the dielectric constant of the sample at room temperature.
[0073] (2) The strain performance test of the lead nickel niobate-based ceramic sample prepared in Comparative Example 1 was performed. The results are as follows: Figure 4 As shown. Figure 4 It can be seen that under an electric field of 20 kV / cm, the sample presents a butterfly-shaped field-induced strain curve, has a high strain hysteresis, and has poor zeroing, which is not conducive to the application in high-precision and long-life drive devices. The high hysteresis coefficient mainly comes from the movement of the irreversible domain wall driven by the external electric field. By comparing Example 2 with Comparative Example 1, it can be seen that Nd ion doping greatly reduces the hysteresis coefficient caused by the irreversible domain wall movement, thereby obtaining a low hysteresis electrostrictive curve.
[0074] Comparative Example 2
[0075] A lead nickel niobate-based ceramic, the chemical formula of which is: Pb 0.99 Nd 0.01 (Ni 1 / 3 Nb 2 / 3 ) 0.66 Ti 0.34 The preparation method of the lead nickel niobate-based ceramic comprises the following steps:
[0076] (1) According to the chemical formula Pb 0.99 Nd 0.01 (Ni 1 / 3 Nb 2 / 3 ) 0.66 Ti 0.34 PbO, NiO, Nb2O5, TiO2, and Nd2O3 were weighed in a stoichiometric ratio of 1:100°C, and then each raw material was placed in a ball mill for 24 hours (the medium for ball milling was anhydrous ethanol, and the mass ratio of the material to anhydrous ethanol was 1:1.2), and then placed in a 100°C oven for drying, and finally placed in an alumina crucible and pre-calcined at 900°C for 4 hours to obtain a pre-calcined powder.
[0077] (2) adding Rhoplex binder to the pre-calcined powder obtained in step (1) (the amount of binder added is 2 wt% of the mass of the pre-calcined powder), then placing it in a ball mill for 24 hours (the medium for ball milling is anhydrous ethanol, and the mass ratio of the material to anhydrous ethanol is 1:1.2), then placing it in a 100° C. oven for drying, and finally placing it in an agate mortar for grinding, sieving, and pressing to obtain a ceramic green body;
[0078] (3) placing the ceramic green body obtained in step (2) into a muffle furnace, heating the temperature to 500° C. at a rate of 2° C. / min and keeping the temperature for 2 hours to remove the binder; then heating the temperature to 1220° C. at a rate of 5° C. / min, keeping the temperature for 2 hours, and cooling the temperature naturally to obtain a dense ceramic;
[0079] (4) The dense ceramic obtained in step (3) was ground and polished to a thickness of 1.2 mm, and then both sides of the polished dense ceramic were silvered to obtain the lead nickel niobate-based ceramic sample of this comparative example.
[0080] Performance testing and characterization:
[0081] (1) The dielectric properties of the lead nickel niobate-based ceramic sample prepared in Comparative Example 2 were tested, and the dielectric constant at room temperature of 1 kHz was 12060. Comparing Example 2 with Comparative Example 2, it can be seen that as the amount of Nd ion doping decreases, the dielectric constant of the sample at room temperature also decreases.
[0082] (2) The field-induced strain performance of the lead nickel niobate-based ceramic sample prepared in Comparative Example 2 was tested. The results are as follows: Figure 5 As shown. Figure 5 It can be seen that under an electric field of 20 kV / cm, the sample presents a butterfly-shaped field-induced strain curve with a high strain hysteresis, and its obvious feature is that under the same applied electric field and removed electric field, there is a large difference in its field-induced strain. This hysteresis phenomenon will not only lead to a decrease in the accuracy and energy loss of the driver during application, but also reduce the service life of the drive device. Comparing Comparative Example 2 with Comparative Example 1 and Example 2, it can be seen that although Comparative Example 2 is doped with a small amount of Nd, the room temperature dielectric constant is improved and the strain hysteresis coefficient is significantly reduced, but its long-range ordered ferroelectric domain structure still exists, resulting in the field-induced strain curve still having a strain hysteresis phenomenon.
[0083] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.
Claims
1. A lead nickel niobate-based electrostrictive ceramic, characterized in that: The chemical formula of the lead nickel niobate-based electrostrictive ceramic is: (1-y) Nd y (Ni 1 / 3 Nb 2 / 3 ) (1-x) Ti x O3, where: 0.31≤x≤0.37, 0.015≤y≤0.
030.
2. A method for preparing the lead nickel niobate-based electrostrictive ceramic according to claim 1, characterized in that: The following steps are involved: (1) PbO, NiO, Nb2O5, TiO2, and Nd2O3 are mixed in a stoichiometric ratio according to the general chemical formula, and the mixture is ball-milled, dried, and pre-calcined to obtain a pre-calcined powder; (2) adding an organic binder to the pre-calcined powder, and sequentially performing ball milling, drying, sieving, and pressing to obtain a ceramic green body; (3) debinding the ceramic green body and then sintering it to obtain a dense ceramic; (4) Polishing and silvering the surface of the dense ceramic to obtain the lead nickel niobate-based electrostrictive ceramic.
3. The method for preparing lead nickel niobate-based electrostrictive ceramics according to claim 2, characterized in that: In step (1) and step (2), the medium for ball milling is anhydrous ethanol or water.
4. The method for preparing lead nickel niobate-based electrostrictive ceramics according to claim 3, characterized in that: The mass ratio of the ball-milled raw material to the ball-milled medium is 1:(1-1.5).
5. The method for preparing lead nickel niobate-based electrostrictive ceramics according to claim 3, characterized in that: The rotation speed of the ball mill is 200-300 r / min; and / or the time of the ball mill is 12-24 hours.
6. The method for preparing lead nickel niobate-based electrostrictive ceramics according to claim 2, characterized in that: In step (1), the pre-firing temperature is 850-950° C.; and / or the pre-firing time is 2-4 hours.
7. The method for preparing lead nickel niobate-based electrostrictive ceramics according to claim 2, characterized in that: In step (2), the amount of the organic binder added is 2-4wt% of the pre-calcined powder.
8. The method for preparing lead nickel niobate-based electrostrictive ceramics according to claim 2, characterized in that: In step (3), the debinding temperature is 500-700° C.; and / or the debinding time is 1-2 hours.
9. The method for preparing lead nickel niobate-based electrostrictive ceramics according to claim 2, characterized in that: In step (3), the sintering temperature regime is: heating to 1190-1250°C at a rate of 2-5°C / min, keeping the temperature for 1-2 hours; and then naturally cooling to room temperature.
10. An electronic component, characterized in that: It comprises the lead nickel niobate-based electrostrictive ceramic as claimed in claim 1.